FRI0394 MAINTAINED CLINICAL REMISSION IN ANKYLOSING SPONDYLITIS PATIENTS SWITCHED FROM REFERENCE INFLIXIMABTO ITS BIOSIMILAR. AN 18-MONTH COMPARATIVE OPEN-LABEL STUDY. (June 2019) - Kaltsonoudis, Evripidis; Pelechas, Eleftherios; Voulgari, Paraskevi; Drosos, Alexandros; ,
Abstract : Background: switching from reference infliximab (RI) to biosimilar infliximab (BI) had no detrimental effects on efficacy and safety compared to continuous RI. However, long-term follow-up data is missing. Objectives: the aim of this study was to evaluate if BI is equivalent to RI to maintain patients with Ankylosing Spondylitis (AS) in clinical remission, in a long-term fashion. Methods: one hundred and nine consecutive unselected AS patients were investigated. All, followed-up at predefined times receiving RI (5mg/kg/8 weeks) and were naïve to other biologics. Patients who were in clinical remission were asked to switch from RI to BI using the same therapeutic dose. Patients switched to BI were compared with a match control group receiving continuous RI. During follow-up the demographic, clinical, laboratory parameters and comorbidities were all recorded for at least 18 months. Disease activity was measured using the Bath Ankylosing Spondylitis activity index (BASDAI), and the Ankylosing Spondylitis disease activity score (ASDAS), using the C-reactive protein. Remission was defined if patients achieved BASDAI <4 and ASDAS <1.3. Results: twenty-one patients were excluded, nine because had no clinical remission and twelve because refused to switch. Thus, 88 were evaluated. From those, 45 switched to BI, while 43 continued receiving RI. There were no differences between groups regarding demographic, clinical and laboratory parameters. All patients were in clinical remission (BASDAI <4 and ASDAS <1.3). During follow-up, five patients from the switched group and three from the maintenance group discontinued the study. Four patients receiving BI presented nocebo effects and were switched back to the RI. Three responded well, while the fourth did not. After 18 months of treatment, all patients in both groups remained in clinical remission. No significant adverse events were noted between groups. Conclusion: BI is equivalent to RI in maintaining AS in clinical remission for at least 18 months. Acknowledgement: We have no acknowledegement for this abstract Disclosure of Interests: None declared